2014
DOI: 10.1128/mcb.01567-13
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of Histone Gene Regulation Is Obligatory for Genome Replication and Stability

Abstract: bFidelity of chromatin organization is crucial for normal cell cycle progression, and perturbations in packaging of DNA may predispose to transformation. Histone H4 protein is the most highly conserved chromatin protein, required for nucleosome assembly, with multiple histone H4 gene copies encoding identical protein. There is a long-standing recognition of the linkage of histone gene expression and DNA replication. A fundamental and unresolved question is the mechanism that couples histone biosynthesis with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 60 publications
(65 reference statements)
1
44
0
Order By: Relevance
“…80 Similarly, depletion of HiNF-P from cultured cells results in a dispersion of HLBs into smaller bodies, although they still form. 81,82 These data indicate that HiNF-P is not required for mammalian HLB formation but may promote complete HLB assembly via its role in H4 transcription.…”
Section: Self-organization Of the Hlbmentioning
confidence: 87%
“…80 Similarly, depletion of HiNF-P from cultured cells results in a dispersion of HLBs into smaller bodies, although they still form. 81,82 These data indicate that HiNF-P is not required for mammalian HLB formation but may promote complete HLB assembly via its role in H4 transcription.…”
Section: Self-organization Of the Hlbmentioning
confidence: 87%
“…Consistent with a central role in histone gene expression is the synthetic lethality observed upon loss of the individual SAGA subunits Spt8, Spt20, and Gcn5 with deletion of the histone transcriptional activator Spt10 (Chang and Winston 2013). Normal cell cycle progression and DNA repair require precise regulation of histone levels (Singh et al 2009;Singh et al 2010;Eriksson et al 2012;Liang et al 2012;Ghule et al 2014), therefore restoration of histone expression likely contributes to the restored cell cycle progression and growth upon DNA damage that we observe in gcn5D cells overexpressing RTS1.At the end of S phase, Wee1 phosphorylates H2B-Y40 at histone gene promoters to downregulate expression (Mahajan et al 2012), but a counteracting phosphatase is unknown. Future work should determine whether PP2A Rts1 directly dephosphorylates H2BY40ph as part of the mechanism of histone gene activation.…”
mentioning
confidence: 92%
“…[9][10][11][19][20][21] Our recent findings indicated that Hinfp-mediated control of histone H4 gene expression during S phase is essential for cell growth and proliferation. [22][23][24] Complete ablation of Hinfp in mice causes early embryonic lethality between embryonic day (E) 3.5 and E6.5. In vitro cultures of Hinfp-null embryos at E3.5 exhibit abnormal growth and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Our studies also demonstrated that conditional removal of Hinfp in mouse embryonic fibroblasts (MEFs) resulted in reduced expression of histone H4 transcripts as well as protein and subsequently caused a spectrum of cell cycle and proliferation defects. 24 Inactivation of Hinfp and consequential reduction in histone H4 expression directly impacted nucleosomal assembly and generated replicative stress both during interphase and mitosis. 24 Thus, Hinfp may be a key regulatory factor that controls genomic stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation